National Urban Wastewater Treatment Program: Assessment of Task Implementation - Lipińska, Danuta (Comparative Economic Research. Central and Eastern Europe, 2011)
This paper presents an assessment of the state of advancement of work on tasks encompassed by the National Urban Wastewater Treatment Program that are vital in meeting the transitional goals as defined in the Poland's Treaty of Accession to the European Union in the section relating to Council Directive 91/271/EEC concerning urban wastewater treatment. Reasons behind delays in completing planned projects with respect to deadlines earmarked in the National Urban Wastewater Treatment Program are discussed, as are the consequences of the delays. Environmental effects in the area of biodegradable pollutants as achieved in 2009 in terms of individual voivodeships and the country as a whole have also been calculated.